The Role and Governance of the IMF : Further Reflections on Reform. (Pamphlet Series; Pamphlet Series, No., 2009)
This paper reports the second event organized by the Per Jacobsson Foundation in 2008 that took place on Sunday, October 12, in the auditorium of the International Finance Corporation in Washington, DC, in the context of the Annual Meetings of the IMF and the World Bank. From time to time-usually every two years-an additional event is organized in conjunction with the Bank for International Settlements and held in the context of its Annual General Meeting in Switzerland. The Per Jacobsson Foundation was established in 1964 to commemorate the work of Per Jacobsson, the third Managing Director of the IMF (1956-1963) and prior to that, the head of the Monetary and Economic Department of the Bank for International Settlements (1931-1956). The main purposes of the Foundation are to foster and stimulate discussion of international monetary problems, to support basic research in this field, and to disseminate the results of these activities.